Direct‐acting antivirals ability to clear intestinal HCV‐RNA in liver transplant patients. Issue 5 (21st June 2020) - Pietrosi, Giada; Russelli, Giovanna; Barbera, Floriana; Curcio, Gabriele; Tuzzolino, Fabio; Gallo, Alessia; Volpes, Riccardo; Vizzini, Giovanni; Conaldi, Pier Giulio
Abstract: The hepatitis C virus mainly infects the liver but is also able to infect and replicate in other body compartments by creating an extra‐hepatic reservoir that may influence the persistence of the infection after transplantation. It is unknown whether antiviral drugs affect the viral extra‐hepatic sites. We evaluated the ability of pegylated/interferon + ribavirin and sofosbuvir + ribavirin to clear the virus from the gastrointestinal mucosa of liver‐transplanted patients with HCV recurrence after transplantation. A total of 51 liver‐transplanted patients, 30 treated with pegylated/interferon + ribavirin (ERA1) and 21 treated with sofosbuvir + ribavirin (ERA2), were enrolled, and blood serum and gastrointestinal tissues analyzed for the presence of HCV‐RNA. In the ERA1 group, the 46.6% of patients had a sustained viral response to antiviral treatment, and gastrointestinal biopsies were positive for HCV in 73.3% of cases, 54.5% of responders, and 45.5% of non‐responders. In the ERA2 group, the 66.6% had a sustained viral response, and gastrointestinal HCV‐RNA was present in the 14.3% of patients, all relapsers. Sofosbuvir + ribavirin cleared the intestinal HCV in 85.7% of patients with recurrent HCV infection, while pegylated/interferon + ribavirin cleared it in 26.6% of treated patients, demonstrating the better effectiveness of new direct antiviral agents in clearing HCV intestinal reservoir.